2009
DOI: 10.1001/archdermatol.2008.566
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Skin Cancer Risk by Those With Ethnic Skin

Abstract: Lee had full access to all of the data in the study and takes responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 4 publications
6
25
0
Order By: Relevance
“…Our study showed that parents of darker‐skinned children demonstrated less appreciation for the dangers of sun exposure, including skin cancer and photoaging, and perceived a protective effect of darker skin against these outcomes. A small number of previous studies have demonstrated that adults with darker skin types tend to perceive a low lifetime risk of skin cancer for themselves, and our results echo these trends . A dark‐skinned phenotype at best confers a relative SPF of 13.4 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our study showed that parents of darker‐skinned children demonstrated less appreciation for the dangers of sun exposure, including skin cancer and photoaging, and perceived a protective effect of darker skin against these outcomes. A small number of previous studies have demonstrated that adults with darker skin types tend to perceive a low lifetime risk of skin cancer for themselves, and our results echo these trends . A dark‐skinned phenotype at best confers a relative SPF of 13.4 .…”
Section: Discussionsupporting
confidence: 84%
“…Past studies have supported that higher rates of sun protection, primarily sunscreen use, correlate with fairer skin phenotype in children . Furthermore, in a study of primarily African‐American children, rates of sun protection appeared low . The specific question of whether darker‐skinned children are more or less likely to receive ideal sun protection than lighter‐skinned children has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the higher susceptibility of lighter skin types to skin cancers including melanoma (Elder, ; Halder and Ara, ; Holman and Armstrong, ; Katsambas and Nicolaidou, ), premature aging (Chung, ; Hourblin et al., ; Nouveau‐Richard et al., ), and pigmentary disorders (Ho and Chan, ). Our results also emphasize the poor total melanin and eumelanin content that can be found even in tan skin types that have been shown to be found not only in Caucasian populations but also in individuals of Asian, Hispanic, African American and African descent, some of whom perceive themselves to be at a lower risk for developing sunburn and skin cancers (Buster et al., ; Kim et al., ). Photoprotection strategies should thus not be limited to lighter skin types but also extended to moderately pigmented skin types and a better characterization on the melanin chemical phenotype may allow an improvement of photoprotection strategies.…”
Section: Discussionsupporting
confidence: 68%
“…This is because tan skin is found not only in caucasian populations but also in individuals of Asian, Hispanic, African and Afro-American descent, some of whom perceive themselves to be at a lower risk for developing sunburn or skin cancers. 35,36 However, sunburn has been reported among Hispanic black, Asian/Pacific islanders and American Indians/Alaska natives. 37 Furthermore, even though skin cancers are less frequent in nonwhite/darkly pigmented individuals, it is often associated with increased morbidity and mortality due to a lack of awareness of these diseases among these populations, associated with a delay in diagnosis.…”
Section: Discussionmentioning
confidence: 99%